The contradictions of e-health intervention experience of users toward its outcome: a systematic review - Leili Mosalanejad; Mahsa Imanian; Zahra Rezaiee (Mashhad University of Medical Sciences, 2021)
Background: Electronic Health is a kind of communication technology that covers a wide range of healthcare activities, from diagnosis to treatment. This study aimed to investigate the conflicts caused by e-health interventions in patients' attitude and its influence on consequences of the disease in a Meta synthesis study.Methods: Present study is a systematic review and meta-synthesis qualitative research according to articles found by Medline searching the keyword "E-health" published, collected, and reviewed from 2000 to 2019,. Then the search was narrowed down using the keywords "qualitative studies", "patients' attitudes", "Patients' view" about E-health. All English texts or abstracts were included in the study. Duplicated remote papers and paper with main and complementary treatment, also, web base, internet, software, and mobile mediated treatment process as an electronic way were included to the search process. All irrelevant, duplicated, and qualitative studies were excluded from study and totally 23 papers were extracted to review.Results: Regarding the effective features of e-health, it has a significant beneficial effect by empowering patients, treatment through supportive networks, changing the traditional therapeutic algorithms in inducing a successful and influential treatment, successful outcomes with functionality, also being flexible and attractive. Patients also referred to its shortcomings in treatment and expressed the ability to implement it with aura, parallel, and non-variable coverage.Conclusions: Due to the perceptions and positive outcomes of the method, it is necessary to consider ways and means to neutralize or minimize the negative effects of technology on treatment, therefore more efficient use of the electronic health system can be achieved.